Les prénoms des élèves : une ressource didactique pour l’enseignant de français - Mouna Lahlah (Multilinguales, 2024)
The aim of this research is to study the pedagogical effects of activities exploiting the symbolic dimension of pupils’ first names in French classes. The issue is as follows : how can the use of first names serve as a relevant didactic resource to enrich French language teaching ? how can the use of first names serve as a relevant didactic resource to enrich French language teaching ? The objective is to analyze the impact of various activities using first names on students’ motivation and learning. The methodology consisted of several stages : initially, a semantic analysis of the first names from a student corpus was conducted to identify their meanings. Subsequently, targeted pedagogical activities are designed based on this analysis (writing workshops, presentations, debates). These activities were then implemented in classrooms and subjected to evaluation. The results highlighted the benefits of these activities in terms of student motivation and active participation. Positive effects were also observed in their oral and written expression skills. The pedagogical exploration of first names appears to lend greater meaning to French language learning.